Transcultural adaptation of grid hamilton rating scale for depression (GRID-HAMD) to Brazilian portuguese and evaluation of the impact of training upon inter-rater reliability - Henrique-Araújo, Ricardo (2014)
GRID-HAMD is a semi-structured interview guide developed to overcome flaws in HAM-D, and has been incorporated into an increasing number of studies. Objectives: Carry out the transcultural adaptation of GRIDHAMD into the Brazilian Portuguese language, evaluate the inter-rater reliability of this instrument and the training impact upon this measure, and verify the raters’ opinions of said instrument. Methods: The transcultural adaptation was conducted by appropriate methodology. The measurement of inter-rater reliability was done by way of videos that were evaluated by 85 professionals beforeand after training for the use of this instrument. Results: The intraclass correlation coefficient (ICC) remained between 0.76 and 0.90 for GRID-HAMD-21 and between 0.72 and 0.91 for GRIDHAMD- 17. The training did not have an impact on the ICC, except for a few groups of participants with a lower level of experience. Most of the participants showed high acceptance of GRID-HAMD, when compared to other versions of HAM-D. Conclusion: The scale presented adequate inter-rater reliability even before training began. Training did not have an impact on this measure, except for a few groups with less experience. GRID-HAMD received favorable opinions from most of the participants.